Multi-objective Optimization Analysis of High Speed Gearbox based on Parametric Design - Gang Haiming; Liu Zhilei; Ge Shixiang (Jixie chuandong)
To improve the static and dynamic characteristics of a high speed gearbox,the main object method of multi-objective optimization is applied in optimization analysis of structures in the high speed gearbox based on parametric design. The simulation results based on ANSYS Workbench prove that,by using multi-objective optimization,the high speed gearbox mass can be reduced,at the same time,the static characteristics,dynamic characteristics and the design efficiency of gearbox are significantly improved,the higher requirements in performance of high speed gearbox is satisfied,and a theoretical guide and reference for the optimization design and improvement of other critical parts of gearbox is provided.